Experimentally validated numerical model of coupled flow, thermal and electromagnetic problem in small power electric motor - Slupik, Lukasz; Smolka, Jacek; Wrobel, Luiz C. (Computer Assisted Methods in Engineering and Science, 2013)
This paper describes results of the mathematical modelling of the steady-state thermal phenomena taking place in a Fracmo 240 W DC electric motor. The model of the motor was defined in the ANSYS Fluent software to predict flow and temperature fields inside the machine. The thermal model was coupled with an electromagnetic solver to determine power losses occurring in different parts of the unit. In order to validate the proposed numerical model, a test rig was set up to measure temperatures at points located inside the motor housing and on its external wall. Additionally, the temperature field was captured by an infrared camera. The results obtained from the coupled analysis are comparable with the measurement data.